2016: A year of looking to the future - CHAN, David (Institutional Knowledge at Singapore Management University, 2016)
Six major events caused Singaporeans to ponder over the future and what it will bring. As 2016 comes to a close, it is timely to reflect on the past 12 months, which I would summarise as "a future-focused year" - one filled with events and issues that made people ponder about their own future and that of the country. It is useful to revisit the way we approached the key events and issues. After all, when it comes to thinking about the future, how we think is as important as what we think.